Association between oxidative balance score and lung function and FeNO and mortality in the US population - Chang Liu; Dan Liang; Guoan Xiang; Kun Xiao; Lixin Xie (BMC Pulmonary Medicine)
Abstract Background The Oxidative Balance Score (OBS) is a new indicator of overall antioxidant/oxidant balance that provides a comprehensive picture of the body's overall oxidative stress status, with higher OBS indicating greater antioxidant exposure. A limited number of studies have examined the association between OBS and lung function and FeNO, and we aimed to investigate the possible relationship between OBS and lung function and FeNO. Methods Data utilized in this study were sourced from the 2007–2012 NHANES. Multivariable logistic regression was employed to investigate the association between OBS/lifestyle OBS (lifestyle antioxidants such as physical activity, etc., and lifestyle pro-oxidants such as alcohol, smoking, etc.)/dietary OBS (dietary antioxidants such as fiber, β-carotene, riboflavin, etc., and dietary pro-oxidants, such as total fat, etc.) and FEV1, FVC, PEF, FEF 25%- 75%, FeNO, as well as obstructive ventilation dysfunction. The dose–response association between the OBS and FEV1, FVC and PEF was explored using RCS analysis. Subgroup analysis and interaction tests were also conducted. We also used multivariable Cox regression modeling to explore the between OBS/lifestyle OBS/dietary OBS and all-cause and respiratory-related mortality. Results A total of 8,568 participants were enrolled. A statistically significant association was observed between OBS/lifestyle OBS/dietary OBS and FEV1, FVC, and PEF levels. There was no statistical association between OBS, lifestyle OBS, dietary OBS, and FeNO levels. RCS revealed a linear relationship between OBS and both FEV1 and FVC levels. Notably, the positive correlation between OBS and dietary OBS with FEV1 was more significant in male participants. Conversely, the relationship between OBS and FVC levels was influenced by gender and BMI. The effects of the overall OBS, lifestyle OBS, and dietary OBS on lung function parameters were independent of whether participants had restrictive ventilatory dysfunction or obstructive ventilatory dysfunction.In addition, both the overall OBS and dietary OBS demonstrated significant inverse associations with all-cause mortality, whereas no statistically significant relationships were observed between these scores and respiratory-related mortality. Notably, only lifestyle OBS exhibited a significant inverse association with respiratory-related mortality. Conclusion In this study, OBS, lifestyle OBS, and dietary OBS levels were positively correlated with lung function parameters (FEV1, FVC and PEF) in U.S. adults. Exploring this association can enhance our understanding of how oxidative homeostasis influences lung function changes. This could provide valuable interventions for lung function decline. We also found that higher OBS was associated with lower all-cause mortality. Adopting a healthy lifestyle and consuming an antioxidant-rich diet may significantly improve the prognosis of patients by reducing oxidative stress-related damage.